Historians and the Church of England: religion and historical scholarship, c.1870-1920 - Kirby, J (2014)
The years 1870 to 1920 saw an extraordinary efflorescence of English historical writing, dominated by historians who were committed members of the Church of England, many of them in holy orders. At a time when both history and religion were central to cultural life, when history was becoming a modern academic discipline, and when the relationship between Christianity and advanced knowledge was under unprecedented scrutiny, this was a phenomenon of considerable intellectual significance. To understand why this came about, it is necessary to understand the intellectual and institutional conditions in the Church of England at the time. The Oxford Movement and the rise of incarnational theology had drawn Anglicans in ever greater numbers towards the study of the past. At the same time, it was still widely held that the Church of England should be a ‘learned church’: it therefore encouraged scholarship, sacred and secular, amongst its laity and clergy. The result was to produce historians who approached the past with a new set of priorities. The history of the English nation and its constitution was rewritten to show that the church – and especially the medieval church – was the originator and guarantor of modern nationality and liberty. Attitudes to the Reformation shifted from the celebratory to the sceptical, or even the downright hostile. Economic historians even came to see the Reformation as a social revolution – as the origin of modern poverty or capitalism. New and distinctive ideas about progress and divine providence were developed and articulated. Most of all, an examination of Anglican historical scholarship shows the continued vitality of the Church of England and the limitations to the idea that intellectual life was secularised over the course of the nineteenth century. Instead, historiography continued to be shaped by Anglican thought and institutions at this critical stage in its development.